2022
DOI: 10.3390/curroncol29110662
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Healthcare Provider Perspectives on the Implementation of a Web-Based Clinical Communication System for Cancer: A Qualitative Study

Abstract: Previous research has identified communication and care coordination problems for patients with cancer. Healthcare providers (HCPs) have reported communication issues due to the incompatibility of electronic medical records (EMR) software and not being consistently copied on patient reports. We evaluated an asynchronous web-based communication system (“eOncoNote”) for primary care providers and cancer specialists to improve cancer care coordination. The objectives were to examine patients’ perceptions of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…In response to two survey items, PCPs emphasized the need to integrate eOncoNote with their EMRs to avoid having to log into a separate system each time. This is consistent with data from our qualitative interviews [ 18 ], suggesting that EMR integration may be a major factor in successfully incorporating eOncoNote into the clinical workflow. Other studies have also reported similar barriers to adopting internet-based physician communication tools, including slow service, difficulty with accessing information and a time-consuming process [ 26 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In response to two survey items, PCPs emphasized the need to integrate eOncoNote with their EMRs to avoid having to log into a separate system each time. This is consistent with data from our qualitative interviews [ 18 ], suggesting that EMR integration may be a major factor in successfully incorporating eOncoNote into the clinical workflow. Other studies have also reported similar barriers to adopting internet-based physician communication tools, including slow service, difficulty with accessing information and a time-consuming process [ 26 ].…”
Section: Discussionsupporting
confidence: 90%
“…In our qualitative interviews, healthcare providers noted that communication was generally one-directional with cancer specialists sending reports to PCPs by fax. Healthcare providers reported that PCPs were more likely to contact cancer specialists by telephone or fax after the patient completed treatment, in instances where a patient had more complex needs, or if the patient lived far away from the cancer center [ 18 ]. Results from the pRCT demonstrated that patients randomized to the intervention group had an average of three comorbid conditions in the treatment phase, and an average of two comorbid conditions in the survivorship phase [ 17 ], so there may have been less of a need for communication regarding patients who did not have as many illnesses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation